Emergence of Congenital Chagas Disease in Ireland. Issue 7 (7th June 2022) - Stone, Roy G.; Gavin, Patrick; Chiodini, Peter; Nolder, Debbie; McGettrick, Padraig; Keogh, Anna; Mc Entagart, Noel; Drew, Richard; Lambert, Jack; Ferguson, Wendy
Abstract : Chagas disease (CD) is an under-diagnosed tropical disease that is increasingly being observed outside of Latin America. We describe the first 2 infants with congenital Chagas Disease (cCD) in Ireland. Clinicians in nonendemic countries need to be aware of the potential for cCD due to the migration of women from countries of high prevalence.